Using the lower limit of normal for the FEV1/FVC ratio reduces the misclassification of airway obstruction. Issue 12 (11th September 2008) - Swanney, M P; Ruppel, G; Enright, P L; Pedersen, O F; Crapo, R O; Miller, M R; Jensen, R L; Falaschetti, E; Schouten, J P; Hankinson, J L; Stocks, J; Quanjer, P H
Abstract : Aim: The prevalence of airway obstruction varies widely with the definition used. Objectives: To study differences in the prevalence of airway obstruction when applying four international guidelines to three population samples using four regression equations. Methods: We collected predicted values for forced expiratory volume in 1 s/forced vital capacity (FEV1 /FVC) and its lower limit of normal (LLN) from the literature. FEV1 /FVC from 40 646 adults (including 13 136 asymptomatic never smokers) aged 17–90+years were available from American, English and Dutch population based surveys. The prevalence of airway obstruction was determined by the LLN for FEV1 /FVC, and by using the Global Initiative for Chronic Obstructive Lung Disease (GOLD), American Thoracic Society/European Respiratory Society (ATS/ERS) or British Thoracic Society (BTS) guidelines, initially in the healthy subgroup and then in the entire population. Results: The LLN for FEV1 /FVC varied between prediction equations (57 available for men and 55 for women), and demonstrated marked negative age dependency. Median age at which the LLN fell below 0.70 in healthy subjects was 42 and 48 years in men and women, respectively. When applying the reference equations (Health Survey for England 1995–1996, National Health and Nutrition Examination Survey (NHANES) III, European Community for Coal and Steel (ECCS)/ERS and a Dutch population study) to the selected population samples, the prevalence of airway obstruction in healthy never smokers aged over 60 years varied for each guideline: 17–45% of men and 7–26% of women for GOLD; 0–18% of men and 0–16% of women for ATS/ERS; and 0–9% of men and 0–11% of women for BTS. GOLD guidelines caused false positive rates of up to 60% when applied to entire populations. Conclusions: Airway obstruction should be defined by FEV1 /FVC and FEV1 being below the LLN using appropriate reference equations.